Predatory Short Sales and Bailouts - Peter N. Posch; Gunter Löffler; Sebastian Kranz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper extends the literature on predatory short selling and bailouts through a joint analysis of the two. We consider a model with informed short sales, as well as predatory short sales by an uninformed investor, which can trigger the inefficient liquidation of a firm. We obtain several novel results: A goverment commitment to bail out insolvent firms with positive probability can increase welfare because it selectively deters predatory short selling without hampering desirable informed short sales. Contrasting a common view, bailouts can be optimal ex ante but undesirable ex post. Furthermore, bailouts in our model are a better policy tool than short selling restrictions. Welfare gains from the bailout policy are unevenly distributed: shareholders gain while taxpayers lose. Bailout taxes allow ex-ante Pareto improvements.
Keywords: G38; D53; G10; 330